MANAGEMENT OF ROOT ROT DISEASE [MACROPHOMINA PHASEOLINA (TASSI.) GOID] OF CHICKPEA THROUGH BOTANICALS AND OIL CAKES - J. C. DHINGANI,; K. U. SOLANKY,; S. S. KANSARA, (The Bioscan, 2013)
Occurrence of root rot disease in chickpea has become a major constraint for cultivation of chickpea. Considering the fact, below investigation was carried out for this pathological problem. The efficacy of various botanicals and oil cakes were evaluated against Macrophomina phaseolina (Tassi.) Goid causing dry root rot of chickpea. The phyto extracts of thirteen plant species were evaluated in vitro by poisoned food technique against M. phaseolina. The extract of garlic cloves (Allium sativum L.) was proved excellent with maximum inhibiting (73 %) mycelial growth and sclerotial formation followed by rhizome extract of turmeric (Curcuma longa L) (63.98 %). The four organic extracts were tested against M. phaseolina by poisoned food technique in vitro. Significantly least growth of mycelium and maximum mycelium inhibition was recorded in extracts of neem cake (59.40 %) followed by farm yard manure (42.56 %). Next best in order of merit were castor cake and mustard cake.